PENERAPAN TEORI BELAJAR HUMANISTIK PADA MATERI KERAGAMAN BUDAYA UNTUK MENUMBUHKAN SIKAP TOLERANSI SISWA KELAS IV SEKOLAH DASAR - Hidayatna Hidayatna; Ryan Dwi Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the application of humanistic theory to the material of cultural diversity and test its effectiveness in fostering tolerance attitudes in fourth-grade elementary school students. The study used descriptive qualitative methods with observation, interviews, and questionnaires. The subjects were 36 fourth-grade students of Lembang Elementary School. The background of this study is because of the continued discovery of behavior that does not respect or does not accept differences such as teasing, isolating friends, negative prejudice, and a lack of mutual assistance among elementary school students of different cultural backgrounds. Humanistic learning theory with a student-centered learning approach positions students as unique individuals, with diverse backgrounds, needs, interests, and abilities. In the context of student diversity in schools, student management must be carried out with compassion (empathy) by paying attention to their emotional, social, and psychological aspects, so that the learning atmosphere can take place safely, comfortably, and pleasantly. Humanistic-oriented student management not only emphasizes academic achievement, but also the development of human values ​​such as respecting differences among others, mutual respect, and attitudes of mutual love and help. The application of humanistic learning theory is highly effective in fostering tolerance in fourth-grade elementary school students on cultural diversity. The results of this study indicate that the application of humanistic learning theory through student-centered learning activities, respect for differences, and the provision of freedom of expression can create a humanistic and meaningful learning environment. Students' tolerance significantly increased, as evidenced by indicators such as respect for differences, cooperation in groups, and acceptance of peers from different cultural backgrounds. This study recommends a humanistic approach for character education in elementary schools.